KONSEP UANG DALAM EKONOMI MAKRO ISLAM - Amelia, Rika Nur; Afiqul Rifqi, Muhammad; Latifah, Eny (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This article discusses the concept of money in Islamic macroeconomics through library study methods, focusing on the fundamental differences between money concepts in the Islamic economy and conventional economics. The study explores monetary policy in the view of the Islamic economic system as well as identifying obstacles and challenges in the application of Islamic economy in the modern world. In Islamic economics, money is not only a tool of exchange but also contains strong moral and ethical values, unlike conventional economics which emphasizes more on technical functions and merely profit. Islamic monetary policy, based on the principles of Shariah, aims to create economic justice and social well-being. The challenges faced in implementing this system include lack of understanding and acceptance, as well as inadequate institutional infrastructure. This article concludes that despite significant obstacles, the implementation of Islamic monetary and monetary policy concepts has great potential to correct global economic injustice if implemented comprehensively and supported by a proper policy framework.